2018 AIAA Aerospace Sciences Meeting 2018
DOI: 10.2514/6.2018-0358
|View full text |Cite
|
Sign up to set email alerts
|

Unsteady Heat Flux Measurements of Junction Flow With Reynolds Number and Freestream Turbulence Effects

Abstract: Turbulent junction flow is a three-dimensional unsteady phenomenon occurring in the flow upstream of the leading edge of bodies attached to a surface, such as in turbine rotors and stators, heat exchangers, submarine appendages, and wing-fuselage attachments. One of the signature features of this type of flow is the presence of bimodal behavior in the probability density functions of velocity, but the bimodal phenomenon has not been observed in surface heat flux measurements. However, it is well-known that tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
1
1
0
Order By: Relevance
“…and at high Reynolds number, appears to have the effect of insulating the horseshoe vortex, which is contained entirely within the boundary layer, from freestream turbulence. This observation agrees with the findings of a companion publication by Elahi, et al [21], which suggests that the effect of freestream turbulence on surface heat transfer produced by the horseshoe vortex is observed most strongly at low Reynolds number and decrease with increasing Reynolds number for a given freestream turbulence level.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…and at high Reynolds number, appears to have the effect of insulating the horseshoe vortex, which is contained entirely within the boundary layer, from freestream turbulence. This observation agrees with the findings of a companion publication by Elahi, et al [21], which suggests that the effect of freestream turbulence on surface heat transfer produced by the horseshoe vortex is observed most strongly at low Reynolds number and decrease with increasing Reynolds number for a given freestream turbulence level.…”
Section: Discussionsupporting
confidence: 92%
“…A detailed table of estimations of uncertainty in the SPIV measurements of this study may be found in Elahi, et al [18]. An analysis of uncertainty in the hotwire measurements was conducted via the method described in Moffat [21], with the resulting uncertainty in velocity measurement over the range of velocities measured in this study at 2.6 percent.…”
Section: Measurement Uncertaintymentioning
confidence: 99%